2022
DOI: 10.1002/cyto.b.22108
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter flow cytometry in the evaluation of myelodysplasia: Analytical issues

Abstract: Multiparameter flow cytometry (MFC) is one of the essential ancillary methods in bone marrow (BM) investigation of patients with cytopenia and suspected myelodysplastic syndrome (MDS). MFC can also be applied in the follow-up of MDS patients undergoing treatment. This document summarizes recommendations from the International/European Leukemia Net Working Group for Flow Cytometry in Myelodysplastic Syndromes (ELN iMDS Flow) on the analytical issues in MFC for the diagnostic work-up of MDS. Recommendations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 192 publications
2
19
0
Order By: Relevance
“…Multivariable Cox regression analysis including iFS, IPSS-R (as a whole or with its single components), and age showed that iFS could add independent prognostic information beyond IPSS-R (p = 0.0078: The WHO 2016 classification of myeloid neoplasms lists the presence of immunophenotypic aberrancies measured by FCM as a co-criterion for MDS, but FCM based findings alone are not sufficient to establish the diagnosis (Arber et al, 2016). Since a decade, iMDSFlow has been promoting standardization of pre-analytical and analytical work up in MDS FCM (Porwit et al, 2014;Porwit et al, 2021;van de Loosdrecht et al, 2009;Van der Felden et al, 2021;Westers et al, 2012). To our knowledge, our prospective cohort study compared for the first time widely used diagnostic MDS FCM-scores in a large number of BM samples from MDS patients, healthy (HBM), as well as pathological controls (NCC).…”
Section: Impact Of Ifs On Overall Survival (Os)mentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariable Cox regression analysis including iFS, IPSS-R (as a whole or with its single components), and age showed that iFS could add independent prognostic information beyond IPSS-R (p = 0.0078: The WHO 2016 classification of myeloid neoplasms lists the presence of immunophenotypic aberrancies measured by FCM as a co-criterion for MDS, but FCM based findings alone are not sufficient to establish the diagnosis (Arber et al, 2016). Since a decade, iMDSFlow has been promoting standardization of pre-analytical and analytical work up in MDS FCM (Porwit et al, 2014;Porwit et al, 2021;van de Loosdrecht et al, 2009;Van der Felden et al, 2021;Westers et al, 2012). To our knowledge, our prospective cohort study compared for the first time widely used diagnostic MDS FCM-scores in a large number of BM samples from MDS patients, healthy (HBM), as well as pathological controls (NCC).…”
Section: Impact Of Ifs On Overall Survival (Os)mentioning
confidence: 99%
“…Therefore, additional diagnostic procedures as histology, molecular sequencing analyses, and flow cytometry (FCM) have to be conducted (Valent et al, 2017). FCM as one of these methods is subjected to several standardization efforts within the iMDS Flow working group (iMDSFlow) of the European leukemia net (ELN) in the last decade (Porwit et al, 2014; van de Loosdrecht et al, 2009; Westers et al, 2012); this issue is addressed in more detail in three separate papers in this special issue of Cytometry Part B: Clinical Cytometry (Porwit et al, 2021; van de Loosdrecht et al, 2021; Van der Felden et al, 2021). Several diagnostic MDS FCM‐scores have been published, for example, FCM scoring system (FCSS, Wells et al, 2003) mainly analyzing granulo‐ and monopoiesis, Ogata‐score (Della Porta et al, 2012; Ogata et al, 2009) focusing on progenitor cells, RED‐score and ELN‐NEC (Mathis et al, 2013; Westers et al, 2017) with an emphasis on nucleated erythropoietic cells (NEC), and integrated flow‐score (iFS, Cremers et al, 2017) comprising aspects of all the aforementioned FCM‐scores (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines recommend flow cytometric analysis as part of the diagnostic work‐up of cytopenic cases suspected for myelodysplastic syndromes (MDS) (Porwit et al, 2014 ; Porwit et al, 2022 ; Valent, Orazi, et al, 2017 ; van de Loosdrecht et al, 2023 ). Many reports on flow cytometry (FCM) in MDS focus on examples of aberrant immunophenotypic features without putting the results of a single patient in the context of clinical features and other diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%
“…In MDS, both CD13 and CD16 expression may be increased and/or decreased in all or some maturational stages. MDS‐FCM guidelines stress that upon loss of CD16, one should consider the presence of paroxysmal nocturnal hemoglobinuria (PNH)‐type cells, especially in combination with loss of CD14 on mature monocytes (Porwit et al, 2014; Porwit et al, 2022; Westers et al, 2012). Of note, changes in CD16 expression may also result from apoptosis, aged specimen, eosinophils that contaminate the neutrophil gate, Fc gamma receptor IIIb polymorphisms, or familial gene deficiency (de Haas et al, 1995; Dransfield et al, 1994; Loken et al, 2009; Stachurski et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of bone marrow (BM) samples enables evaluation of dysplastic features in progenitor cells and maturing subsets such as granulocytes, monocytes, and erythroid cells. Non-clonal cytopenic cases often serve as controls whereas normal BM samples are used to establish reference patterns and cut-off values for aberrant marker expression (Porwit et al, 2014(Porwit et al, , 2022Westers et al, 2012).…”
Section: Introductionmentioning
confidence: 99%